2004
DOI: 10.1038/nm1169
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-print and print-phoresis as platform technologies for the molecular analysis of human surgical specimens: mapping tumor invasion of the prostate capsule

Abstract: Molecular profiling of human biopsies and surgical specimens is frequently complicated by their inherent biological heterogeneity and by the need to conserve tissue for clinical diagnosis. We have developed a set of novel 'tissue print' and 'print-phoresis' technologies to facilitate tissue and tumor-marker profiling under these circumstances. Tissue printing transfers cells and extracellular matrix components from a tissue surface onto nitrocellulose membranes, generating a two-dimensional anatomical image on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…4 Prostate tissue prints were snap-frozen immediately on collection and stored at Ϫ80°C before processing; each tissue print was sliced into a set of 5 ϫ 5-mm tiles for biomarker extraction. Print collection and processing was performed in an oriented manner (with fiduciary markers) so that FFPE samples from corresponding tumor sites could be identified for DNA analysis.…”
Section: Sources and Extraction Of Human Genomic Dnamentioning
confidence: 99%
See 2 more Smart Citations
“…4 Prostate tissue prints were snap-frozen immediately on collection and stored at Ϫ80°C before processing; each tissue print was sliced into a set of 5 ϫ 5-mm tiles for biomarker extraction. Print collection and processing was performed in an oriented manner (with fiduciary markers) so that FFPE samples from corresponding tumor sites could be identified for DNA analysis.…”
Section: Sources and Extraction Of Human Genomic Dnamentioning
confidence: 99%
“…These archived samples contain a wealth of genetic information and offer a great potential for discovery and analysis of biomarkers with diagnostic and therapeutic significance. 1,2 Laser capture microdissected (LCM) samples, 3 tissue print micropeels, 4 and plasmacirculating DNA 5 are additional sources of valuable clinical material with major potential for discovery and evaluation of cancer biomarkers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to effectively collect margin specimens from the wider area of an irregular deep margin surface, we employed an innovative margin imprint procedure using nitrocellulose membrane to harvest DNA. Gaston, et al, first reported this approach for prostate specimens and extracted RNA from the cells collected on the membrane surface 18 . Our group adapted the procedure to collect DNA from imprint samples 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In the Symposium: ''Discovery and Development of TissueBased Biomarkers in Prostate Cancer,'' B.S. Knudsen (USA) introduced this topic based on novel technological advances of analysis of genomic and proteomic expression in prostate tumors (Chen et al, 2004;Yu et al, 2004); P. Nelson (USA) focused on the fact that molecular correlates of pathological and clinical observations may provide resources for studies designed to determine mechanisms of cancer behavior; A.M. DeMarzo (USA) showed that the earliest phase of human prostate carcinogenesis may proceed as a consequence of chromosomal instability mediated by shortened, dysfunctional telomeres (Lapointe et al, 2004); M. Rubin (USA) provided an approach to validation of candidate genes to use as biomarkers for prostate cancer progression using tissue microarrays (Gaston et al, 2005); and C.C. Collins (USA) showed the use of array Comparative Genomic Hybridation (aCGH) to analyze a cohort of patients indicating that aCGH profiles revealed numerous recurrent copy number aberrations associated to different stages of this cancer.…”
mentioning
confidence: 99%